How SMEs in South Africa can implement robotics to increase competitiveness - Mpungose, Senzo Calvin (University of the Witwatersrand, Johannesburg, 2023)
Orientation: South African SMEs face technology adoption challenges. The Fourth Industrial Revolution (4IR) technologies are no exception. However, SMEs need to gain knowledge on how these technologies affect them. More specifically, how can they benefit from the technologies. Research Purpose: This article investigates the impact of robotics and automation on Small and Medium Enterprises (SMEs) in South Africa. It seeks to identify ways in which the technology could be adopted and with its adoption, improve SME competitiveness. Motivation: The technologies identified as the driving forces behind the 4IR have largely been identified so based on their impact on business and industry. They have led to market convergence which has enabled businesses to operate outside of their industries and markets, thereby increasing market competition. There has been low uptake of robotics and automation in South African SMEs compared to international counterparts and even with the technology viewed as capable of improving business operations, lowering costs and driving competitiveness. Research Design, Approach and Method: A narrative design with interpretivist philosophy utilizing the semi-structured interview schedule to collect data and narrate the views and experiences of participants so as to extrpolate findings was used. Knowledge in this kind of study is subjectively relative to the SMEs being analysed and hence a relativism epistemological stance was taken. The inductive qualitative approach was used to identify patterns from interviews and develop explanations for those patterns. A sample with a fair representation of SMEs that have and have not adopted robotics and automation was interviewed. The interview schedule had nine questions aimed at answering the research questions. Main Findings: The primary reason SMEs adopt robotics and automation is to drive production efficiency, reduce operational costs and increase capacity. SMEs face adoption challenges that include financing, skills shortages and information scarcity. Strategies to overcome these challenges were identified and include finding alternative forms of financing, upskilling existing labour and information dissemination through planned programs. Practical/managerial implications and Contribution/value-add: The study has developed a model that can be used to adopt robotics and automation as well as other 4IR technologies. Strategies that SMEs can use to increase competitivity through the adoption of robotics have been provided alongside strategies to adopt robotics and automation.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: SMEs; Competitiveness; Robotics; Adoption; Production efficiency, 4iR; Production efficiency; 4iR; UCTD; SDG-8: Decent work and economic growth